Opportunities and challenges in enhancing sciences, technology, and innovation mechanisms and policies for sustainable development goals in the new context in Vietnam: some initial analysis and reviews - Nguyen Phuong Chi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
transformations toward completing the 2030 Agenda for sustainable development goals (SDGs). However, STI research are poorly aligned with the SDGs, such as complex underlying social issues of deprivation, inequality, conflict, and climate change. Currently, STI funding has not responded to sustainable development challenges. Substantially more interdisciplinary and transdisciplinary research areas are needed, including research from the social sciences and humanities, physical sciences and engineering, life and health sciences, computer science, and mathematics. The article has analyzed the STI background and current issues, STI challenges, proposed solutions to contribute to the SDGs, and the synergies and tensions among the SDG goals. Code: